Response to “Prevalence, Risk Factors, and Mortality of Invasive Pulmonary Aspergillosis in Patients with Anti-MDA5 + Dermatomyositis: A Retrospective Study in China” [Letter] - Prisusanti RD; Suhariyono US; Mahdi C (Dove Medical Press, 2024)
Retno Dewi Prisusanti, Untung Slamet Suhariyono, Chanif Mahdi Medical Record and Health Information Department, ITSK RS DR Soepraoen Malang, Kota Malang, Jawa Timur, IndonesiaCorrespondence: Retno Dewi Prisusanti, ITSK RS DR Soepraoen Malang, Kota Malang, Jawa Timur, Indonesia, Email retnodewi@itsk-soepraoen.ac.id